Двенадцать месяцев: стихи-загадки / И. Мазнин - Мазнин Игорь (Стихи для малышей, 2016)
Экземпляры: ф.7 (20171215) / Инвентарный номер: 54361 / Цена: / Авт.знак: М 13 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6